Association between PTCH1 and RAD54B single‐nucleotide polymorphisms and non‐syndromic orofacial clefts in a northern Chinese population. (5th November 2018) - Liu, Xiaotong; Yang, Shaoyou; Meng, Lingwei; Chen, Chunyu; Hui, Xiang; Jiang, Yuxin; Jiao, Xiaohui; Lv, Kewen; Song, Tao
Abstract: Background: Non‐syndromic orofacial clefts (NSOC) is one of the most common congenital malformations, and its etiology involves both genetic and environmental factors. The present aimed to investigate the association of six single nucleotide polymorphisms (SNPs) (rs10512248 in PTCH1, rs12681366 and rs958447 in RAD54B, rs13317 in FGFR1, rs1838105 and rs4968247 in WNT9B) with NSOC in a Northern Chinese population. Methods: In the present study, HI‐SNP technology was used to conduct genotyping of the six SNPs (rs10512248, rs12681366, rs957448, rs13317, rs1838105 and rs4968247) in 596 patients with NSOC and 466 healthy individuals from a Northern Chinese population. Results: The results obtained indicated that rs10512248 and rs12681366 minor allele frequencies were statistically significant ( p  = 0.020 and 0.015, respectively). Statistical analysis confirmed that the CT genotype of RAD54B rs12681366 was associated with a decreased risk of NSOC (odds ratio = 0.62, 95% confidence interval = 0.46–0.82, P  = 0.001). After correcting for multiple testing, the associations remained significant. By contrast, nonsignificant differences were found for the rs957448, rs13317, rs1838105 and rs4968247 allele and genotype frequencies between cases and controls. Conclusions: These results demonstrate that the PTCH1 rs10512248 and RAD54B rs12681366 were significantly associated with NSOC in a Northern Chinese population. Additionally, the RAD54B rs12381366 CT genotype could decrease the risk of NSOC in a Northern Chinese population. We provide novel evidence for the development of NSOC in a Northern Chinese population.